2017
DOI: 10.1111/josh.12477
|View full text |Cite
|
Sign up to set email alerts
|

How Schools Can Promote Healthy Development for Newly Arrived Immigrant and Refugee Adolescents: Research Priorities

Abstract: These research priorities emphasize the generation of practical knowledge that could translate to immediate, tangible benefits for schools. Funders, schools, and researchers can use these research priorities to guide research for the highest benefit of schools and the newly arrived immigrant and refugee adolescents they serve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 42 publications
0
35
0
1
Order By: Relevance
“…The results also indicated that employed refugees had higher scores for problem solving, and unemployed refugees had higher scores for seeking social support. Having a job is considered an essential financial resource that determines the refugee economic status and enables them to meet their basic needs relating to daily living, health, and education expenses (McNeely et al, 2017; Pfortmueller et al, 2016). A study conducted among Soviet Jewish refugees revealed that employed refugees reported the highest levels of income, acculturation, comfort speaking English, and life satisfaction (Vinokurov, Birman, & Trickett, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results also indicated that employed refugees had higher scores for problem solving, and unemployed refugees had higher scores for seeking social support. Having a job is considered an essential financial resource that determines the refugee economic status and enables them to meet their basic needs relating to daily living, health, and education expenses (McNeely et al, 2017; Pfortmueller et al, 2016). A study conducted among Soviet Jewish refugees revealed that employed refugees reported the highest levels of income, acculturation, comfort speaking English, and life satisfaction (Vinokurov, Birman, & Trickett, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Through immigration, refugees experience many stressful and traumatic situations prior to, during, and after transfer. They face family disturbances, the loss of close relatives, unsafe situations, physical and sexual abuse, bombing, arrest, and torture (Al-Smadi et al, 2017; McNeely et al, 2017; Stewart, Simich, Shizha, Makumbe, & Makwarimba, 2012). Refugees may also experience states of social exclusion or discrimination after migration, which are caused by their exclusion from the social system, lack of social status, increased rates of unemployment, and financial difficulties associated with low levels of services and lack of social containment (Araya, Chotai, Komproe, & deJong, 2011; Gladden, 2012; Henry, 2012; Tippens, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Schools maintain an indispensable role for educating migrant students and reducing achievement disparities. 17 While distance learning may be accessible for some students, limited technological proficiency among refugee families poses a barrier to remote schooling. 13 The isolating conditions created by COVID-19 may have devastating impacts on pediatric refugee health and development.…”
Section: Economic Hardshipmentioning
confidence: 99%
“…The second form of youth action to unpack trapped mobility is related to social and cultural agency. It has been suggested that youth work should stretch from providing immediate aid to training courses and capacity building of displaced youth and provide social rights education to refugees and migrants (McNeely et al 2017;Plener et al 2017).…”
Section: Unpacking Trapped Mobility Youth Responsesmentioning
confidence: 99%